2018
DOI: 10.1002/msc.1365
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of the experiences and perceptions of adults with chronic musculoskeletal conditions following a 12‐week Pilates exercise programme

Abstract: Introduction:The aim of the present study was to explore the experiences and perceptions of adult patients with chronic musculoskeletal conditions following a Pilates exercise programme. A qualitative approach was taken to both data collection and analysis, with alignment to the philosophy of interpretive phenomenology. Participants included 15 women and seven men with a range of chronic musculoskeletal conditions, including nonspecific low back pain, peripheral joint osteoarthritis and a range of postsurgical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 35 publications
(41 reference statements)
2
18
0
3
Order By: Relevance
“…Physiotherapists in the present study perceived the physical benefits These holistic benefits may be significant, particularly for older participants, by reducing levels of inactivity seen as a result of ageing, and improving chronic conditions, as has been demonstrated in a previous study of Pilates (Gaskell & Williams, 2018).…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Physiotherapists in the present study perceived the physical benefits These holistic benefits may be significant, particularly for older participants, by reducing levels of inactivity seen as a result of ageing, and improving chronic conditions, as has been demonstrated in a previous study of Pilates (Gaskell & Williams, 2018).…”
Section: Discussionsupporting
confidence: 61%
“…However, several of the other proposed benefits—such as improved posture and movement control, with carry‐over to some achieving recommended levels of weekly physical activity, continuing at work and hobbies, and facilitation of self‐management—have not been verified by clinical trials (C. Wells, G. S. Kolt, P. Marshall, & A. Bialocerkowski, ). These holistic benefits may be significant, particularly for older participants, by reducing levels of inactivity seen as a result of ageing, and improving chronic conditions, as has been demonstrated in a previous study of Pilates (Gaskell & Williams, ).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Focus group studies have been successfully employed to gain insight into individual experiences and perceptions of exercise programs and to provide information for the development of programs accordingly [ 21 , 22 ]. Using a similar approach to inform the design of a walking program, we conducted a qualitative study with the research question: What key characteristics need to be included in planning and developing a walking program specific for women with moderate to severe menopause symptoms?…”
Section: Introductionmentioning
confidence: 99%
“…However, of the randomized controlled trials (RCTs) reviewed, high levels of heterogeneity were reported, in terms of sample (sub‐types of back pain), exercise selection, delivery and frequency of treatment. In addition, qualitative research evaluating Pilates as a treatment approach is limited, mostly focusing on LBP populations (Gaskell & Williams, ). These methods can be valuable to review the definition, scope and rationale of Pilates treatment methods used by physiotherapists, to provide optimum rehabilitation.…”
Section: Introductionmentioning
confidence: 99%